PENGGUNAAN METODE GIVING QUESTION AND GETTING ANSWER UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI LINGKARAN - Fitriani, Wiwin; Sanapiah, Sanapiah; Pujilestari, Pujilestari (Media Pendidikan Matematika, 2018)
The problems in mathematics needed a madel or appropriate learning methods, one of the models or methods that trains students to ask and answer questions in the learning process is a method of Giving Question and Getting Answers, one method that is expected to improve motivation and learning outcomes students. This study aims to improve motivation and learning outcomes of students of class VIII SMP Negeri 9 Satu Atap Pujut through the application of learning methods Giving Question and Answer Getting the subject matter of the circle in the academic year 2015/2016. This research was conducted in SMP Negeri 9 Satu AtapÂ  Pujut central Lombok district. This research is a classroom action research (PTK) by applying the learning method Giving Getting Question and Answer. This study was conducted in two cycles. The results showed an increase in the average value of the evaluation results of students in each cycle is the first cycle the average value of the results of the evaluation study with classical completeness 67.06 75.86% and 74.17% student motivation with high category. While on the second cycle the average value of the results of the evaluation study with classical completeness 73.65 86.20% and 87.13% student motivation with very high category. From the data obtained, it can be concluded that the application of learning methods Giving Question and Answer Getting may improve motivation and learning outcomes of students of class VIII SMP Negeri 9 Satu Atap Pujut the school year 2015/2016.